On the comprehension of metonymical expressions by Arabic-speaking EFL learners: A cognitive linguistic approach - Zibin Aseel; Altakhaineh Abdel Rahman Mitib; Hussein Elham T. (Topics in Linguistics, 2020)
This study aims to examine the comprehension of L2 metonymies by Arabic-speaking EFL learners and to investigate the extent to which the participants’ L1 conceptual and linguistic knowledge of metonymies can affect the processing of L2 metonymies. A comprehension task was administered to elicit data, and the results showed that the participants encountered various degrees of difficulty comprehending different types of metonymies. Though metonymy has been regarded as a universal cognitive device, numerous factors can collaborate to hinder its comprehension process. The researchers argued that the non-conventionality of conceptual metonymies, the non-compositional nature of metonymy processing, the lack of direct exposure to metonymy as a cognitive referential device in L2, and the differences between L1 and L2 possibly contributed to the participants’ faulty answers on the administered test. The study concluded with a set of pedagogical implications and recommendations for further research studies.